Keterampilan Gerak Dasar Shooting Dalam Permainan Sepakbola Siswa Kelas IV Dan V SD Negeri 7 Baosan Kidul Kecamatan Ngrayun Kabupaten Ponorogo (Eduscotech, 2023)
This research is motivated by Shooting technique is not an easy movement for elementary students. This study aims to determine Shooting Skills in the Game of Students Football Class IV and V SD 7 Baosan Kidul District Ngrayun District Ponorogo. This research is a quantitative descriptive research. The method used is survey method with data retrieval technique by using shooting test instrument. The subjects of this study are all students of grade IV and V of SD Negeri 7 Baosan Kidul, amounting to 33 students. Analytical technique is descriptive statistic by pouring frequency into percentage form.The results of this study indicate that Shooting Skills in the Game of Class and VII Students Football SD Negeri 7 Baosan Kidul is enough with the consideration of most frequencies are in enough category with 12 people or 36.36%. Evaluation of Shooting Skill in the Game of Football of Grade IV and V of SD Negeri 7 Baosan Kidul Sub Ngrayun Sub-Province of Ponorogo which categorized very good 0 people or 0%, either 8 person or 24,24%, enough 12 person or 36,36%, less 8 people 24.24% and less once 5 people or 15.15%.